American policy on fighting drug-trafficking and Plan Colombia (1998-2005) - Santos, Marcelo (FCL-UNESP Laboratório Editorial, 2007)
The article analyses North American policy against drug-trafficking in the post cold war and the advent of Plan Colombia. The main aspects of the US’s foreign policy toward Latin America, mainly Colombia, are examined. The text also analyzes the strategic association between the government of Colombia and the government of US about Plan Colombia.